Building Digital Security Skills for the Future of Work through Education in Indonesia - Nur Azisa Ibrahim; Aquilita Damayanti Nurhan; Almughira Ahmad Kalamor; Wahyu Hidayat; -, Dian Puspita Sari Andri (Jurnal MediaTIK, 2025)
Advances in digital technology have transformed many aspects of life, including communication and work, with widespread internet access in Indonesia. However, challenges such as cyber threats and personal data breaches make digital security skills an urgent need, especially for the younger generation. This study aims to identify the challenges and opportunities in integrating digital security skills into higher education curricula in Indonesia. Using a quantitative approach and descriptive analysis using Jamovi, this study illustrates the needs of students in facing a technology-based workforce. Previous contributions show a focus on general digital literacy, while digital security aspects are still minimal. The results reveal gaps in technical skills mastery and the importance of practice-based curriculum and collaboration with industry. Further research is recommended to evaluate the influence of social factors and the effectiveness of digital security training programs in higher education.